Potential differences in occurrence of preterm births according to quality of relationship between mothers and fathers of the children - Konrádyová, Nika; Rimárová, Kvetoslava; Diabelková, Jana; Urdzík, Peter; Dorko, Erik; Andraščíková, Štefánia (Central European Journal of Public Health, 2022)
OBJECTIVES: Premature birth is a serious pregnancy complication that is affected by many biological as well as psychosocial factors. Several studies have shown that a mother's positive relationship with her child's father reduces the mother's stress, anxiety and depression during pregnancy, promotes a healthier mother's lifestyle and thus has a positive effect on pregnancy as such. This research was therefore aimed at identifying possible differences in the incidence of premature births in mothers depending on the quality of the relationship with the father of their child. METHODS: The research involved 210 mothers after childbirth in the period from October 2020 to September 2021. A questionnaire aimed at obtaining descriptive data about the mother and her child and a questionnaire aimed at determining the quality of the relationship - Quality of Relationship Inventory (QRI) were distributed. Mann-Whitney U tests were used to determine differences between groups. RESULTS: Of 210 children, 44 (21%) were born prematurely, 154 (73.3%) mothers were married and 176 (83.8%) lived with the father of their child in the same household. The results showed that the degree of quality of the mother's relationship with the child's father is approximately the same for mothers who gave birth prematurely and for those who gave birth at term, so there were no differences in this factor between the two groups of mothers. CONCLUSION: The results of other researchers have shown the positive impact of partners on pregnancy and the overall well-being of the mothers. However, our research has not confirmed the positive effect of the quality of the relationship between mother and father of her child on reducing the incidence of premature births. Further research is needed to clarify how specifically and whether the quality of the relationship between parents can affect the incidence of premature births at all.
Keywords: Female; novorozenec; Pregnancy; Humans; Child; těhotenství; Infant, Newborn; komplikace těhotenství; Mothers; Pregnancy Complications; dítě; průzkumy a dotazníky; ženské pohlaví; předčasný porod; Premature Birth; matky; lidé; Surveys and Questionnaires